A Machine Learning Classifier Improves Mortality Prediction Compared With Pediatric Logistic Organ Dysfunction-2 Score: Model Development and Validation. (17th May 2021) - Prince, Remi D.; Akhondi-Asl, Alireza; Mehta, Nilesh M.; Geva, Alon
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To determine whether machine learning algorithms can better predict PICU mortality than the Pediatric Logistic Organ Dysfunction-2 score. Design: Retrospective study. Setting: Quaternary care medical-surgical PICU. Patients: All patients admitted to the PICU from 2013 to 2019. Interventions: None. Measurements and Main Results: We investigated the performance of various machine learning algorithms using the same variables used to calculate the Pediatric Logistic Organ Dysfunction-2 score to predict PICU mortality. We used 10, 194 patient records from 2013 to 2017 for training and 4, 043 patient records from 2018 to 2019 as a holdout validation cohort. Mortality rate was 3.0% in the training cohort and 3.4% in the validation cohort. The best performing algorithm was a random forest model (area under the receiver operating characteristic curve, 0.867 [95% CI, 0.863–0.895]; area under the precision-recall curve, 0.327 [95% CI, 0.246–0.414]; F1, 0.396 [95% CI, 0.321–0.468]) and significantly outperformed the Pediatric Logistic Organ Dysfunction-2 score (area under the receiver operating characteristic curve, 0.761 [95% CI, 0.713–0.810]; area under the precision-recall curve (0.239 [95% CI, 0.165–0.316]; F1, 0.284 [95% CI, 0.209–0.360]), although this difference was reduced after retraining the Pediatric Logistic Organ Dysfunction-2 logistic regression model at the study institution. The random forest model also showed better calibration than the Pediatric Logistic Organ Dysfunction-2 score, and calibration of the random forest model remained superior to the retrained Pediatric Logistic Organ Dysfunction-2 model. Conclusions: A machine learning model achieved better performance than a logistic regression-based score for predicting ICU mortality. Better estimation of mortality risk can improve our ability to adjust for severity of illness in future studies, although external validation is required before this method can be widely deployed.